Analisis Kesulitan Guru dalam Perencanaan, Pelaksanaan, dan Evaluasi Metode Projek pada Pembelajaran Pendidikan Pancasila di SMKN 4 Padang - Khanza Sabina Maharani; Al Rafni; Hasrul Hasrul; Monica Tiara (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze teachers’ difficulties and their strategies in implementing the project method in Pancasila Education at SMKN 4 Padang. Using a descriptive qualitative approach, data were collected through interviews and classroom observations involving teachers and school management. The findings reveal that teachers encounter challenges across three main stages: planning, implementation, and evaluation. In the planning stage, difficulties arise in translating learning outcomes into concrete project activities, designing instructional plans, and aligning them with limited time and resources. During implementation, challenges include time management, low student engagement, classroom dynamics, and limited facilities. In the evaluation stage, teachers face difficulties in developing appropriate assessment instruments, identifying individual contributions in group work, and conducting follow-up on learning outcomes. These findings indicate that the implementation of the project method requires not only teacher competence but also adaptive strategies and strong institutional support to ensure effective and meaningful learning.